An empirical review of the complimentary nature of fundamental and technical analysis techniques based on JSE-listed stocks - Mashiqa, Vuyolwethu Ayanda (My University, 2014)
This study contributes to the debate on whether fundamental analysis and technical analysis techniques can be used jointly in making investment decisions. Extant literature on fundamental and technical analysis techniques has frequently focused on analysing each of the valuation techniques independently of one another. In this study we construct a model that integrates both fundamental and technical analysis variables (hybrid model) to determine whether the hybrid model can have a superior explanatory power to models based on each of the valuation techniques in isolation. This study is based on all ordinary shares that have been listed on the JSE main board between the 2002 and 2012 fiscal years. Testing rejects the complimentary nature of fundamental and technical analysis techniques by showing that the technical analysis model has a superior explanatory power to both the hybrid model and the fundamental analysis model. We also demonstrate that JSE-listed stocks do not exhibit momentum or contrarian effects with respect to return performances and that the fundamental analysis variables that play a significant role in explaining stock price movements of JSE-listed stocks are the book value per share, cash flow per share, earnings per share and dividends per share.
Keywords: Fundamental analysis; Technical analysis; Integration of fundamental and technical analysis